2013
DOI: 10.1089/jpm.2012.0369
|View full text |Cite
|
Sign up to set email alerts
|

Anatomopathological Causes of Death in Patients with Advanced Cancer: Association with the Use of Anticoagulation and Antibiotics at the End of Life

Abstract: The results of this retrospective study demonstrate that causes of death did not change with the modification of our practice. The high rate of pulmonary infection and embolism in this population, including in patients who received broad spectrum and prophylactic anticoagulation should encourage us to pursue other prospective studies to actually demonstrate the benefit of these treatments in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…With regards to PCU, a retrospective analysis at Genevan PCU showed that TPX was used in 43% of cancer patients [18]. Likewise, the TPX prevalence was high (44%) in a French study, which enrolled 1199 PCU patients, 91% of whom were cancer patients [19].…”
Section: Prevalence Of Thromboprophylaxis In Hospices and Palliative mentioning
confidence: 99%
“…With regards to PCU, a retrospective analysis at Genevan PCU showed that TPX was used in 43% of cancer patients [18]. Likewise, the TPX prevalence was high (44%) in a French study, which enrolled 1199 PCU patients, 91% of whom were cancer patients [19].…”
Section: Prevalence Of Thromboprophylaxis In Hospices and Palliative mentioning
confidence: 99%
“…Many studies reported a high prevalence of thromboprophylaxis use in palliative care units in Switzerland, 36 France, 37 Canada, 3 and Austria 38 ranging from 42% to 49% which is similar to non‐cancer patients, 38 although the high tendency for discontinuation within 72 h of admission 3,36–38 . On the other hand, other studies reported much lower use of thromboprophylaxis (<7%) 21,35,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Measurable parameters in the blood suggest a systemic inflammatory response including: elevated CRP, IL-6 and other pro-inflammatory cytokines, hypoalbuminaemia, leucocytosis and neutrophilia. Interestingly, post-mortem studies demonstrated evidence of silent pneumonia in advanced cancer [80,81]. Although it is not possible to assume causation, these findings are of clinical and research interest.…”
Section: Discussionmentioning
confidence: 99%